A Significant but Rather Mild Contribution of T286 Autophosphorylation to Ca(2+)/CaM-Stimulated CaMKII Activity - Coultrap, Steven J. (Public Library of Science, 2012)
BACKGROUND: Autophosphorylation of the Ca(2+)/calmodulin (CaM)-dependent protein kinase II (CaMKII) at T286 generates partially Ca(2+)/CaM-independent “autonomous” activity, which is thought to be required for long-term potentiation (LTP), a form of synaptic plasticity thought to underlie learning and memory. A requirement for T286 autophosphorylation also for efficient Ca(2+)/CaM-stimulated CaMKII activity has been described, but remains controversial. METHODOLOGY/PRINCIPAL FINDINGS: In order to determine the contribution of T286 autophosphorylation to Ca(2+)/CaM-stimulated CaMKII activity, the activity of CaMKII wild type and its phosphorylation-incompetent T286A mutant was compared. As the absolute activity can vary between individual kinase preparations, the activity was measured in six different extracts for each kinase (expressed in HEK-293 cells). Consistent with measurements on purified kinase (from a baculovirus/Sf9 cell expression system), CaMKII T286A showed a mildly but significantly reduced rate of Ca(2+)/CaM-stimulated phosphorylation for two different peptide substrates (to ∼75–84% of wild type). Additional slower CaMKII autophosphorylation at T305/306 inhibits stimulation by Ca(2+)/CaM, but occurs only minimally for CaMKII wild type during CaM-stimulated activity assays. Thus, we tested if the T286A mutant may show more extensive inhibitory autophosphorylation, which could explain its reduced stimulated activity. By contrast, inhibitory autophosphorylation was instead found to be even further reduced for the T286A mutant under our assay conditions. On a side note, the phospho-T305 antibody showed some basal background immuno-reactivity also with non-phosphorylated CaMKII, as indicated by T305/306A mutants. CONCLUSIONS/SIGNIFICANCE: These results indicate that Ca(2+)/CaM-stimulated CaMKII activity is mildly (∼1.2–1.3fold) further increased by additional T286 autophosphorylation, but that this autophosphorylation is not required for the major part of the stimulated activity. This indicates that the phenotype of CaMKII T286A mutant mice is indeed due to the lack of autonomous activity, as the T286A mutant showed no dramatic reduction in stimulated activity.